2014
DOI: 10.1158/1541-7786.mcr-14-0191
|View full text |Cite
|
Sign up to set email alerts
|

SMAD4 Suppresses AURKA-Induced Metastatic Phenotypes via Degradation of AURKA in a TGFβ-Independent Manner

Abstract: SMAD4 has been suggested to inhibit the activity of the WNT/b-catenin signaling pathway in cancer. However, the mechanism by which SMAD4 antagonizes WNT/b-catenin signaling in cancer remains largely unknown. Aurora A kinase (AURKA), which is frequently overexpressed in cancer, increases the transcriptional activity of b-catenin/T-cell factor (TCF) complex by stabilizing b-catenin through the inhibition of GSK-3b. Here, SMAD4 modulated AURKA in a TGFb-independent manner. Overexpression of SMAD4 significantly su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 52 publications
(78 reference statements)
0
27
0
Order By: Relevance
“…To further confirm, a bimolecular fluorescence complementation (BiFC) assay was performed as previously described. 25 This clearly showed that AIMP1 mainly associated with Smad2 and Smad3 in the cytoplasm (Figure 1b). Competition assay using myc-AIMP1 decreased the interaction between FLAG-VN173-AIMP1 and HA-VC155-Smad2/3 in a dose-dependent manner, further confirming the association of AIMP1 with Smad2 and Smad3 (Figure 1c).…”
Section: Resultsmentioning
confidence: 84%
“…To further confirm, a bimolecular fluorescence complementation (BiFC) assay was performed as previously described. 25 This clearly showed that AIMP1 mainly associated with Smad2 and Smad3 in the cytoplasm (Figure 1b). Competition assay using myc-AIMP1 decreased the interaction between FLAG-VN173-AIMP1 and HA-VC155-Smad2/3 in a dose-dependent manner, further confirming the association of AIMP1 with Smad2 and Smad3 (Figure 1c).…”
Section: Resultsmentioning
confidence: 84%
“…Results from previous studies have suggested that the overexpression of AURKA increases the level of p-GSK-3β, p-Akt1 and β-catenin and plays an important role in cell proliferation, tumor progression and metastasis [4042]. MLN8237 is a specific inhibitor of AURKA [43].…”
Section: Discussionmentioning
confidence: 99%
“…Procedure details were described previously [25] , [26] . The detailed procedure is listed in the supplementary materials and methods.…”
Section: Methodsmentioning
confidence: 99%